Influence of ruminal butyrate supply on net nutrient production and absorption in steers - C.R. Krehbiel; D.L. Harmon; J.E. Schneider (Kansas Agricultural Experiment Station Research Reports, 1990)
Six Holstein steers were used to evaluate the effects of increasing ruminal butyrate on net nutrient production and absorption by the gastrointestinal tract and liver. Ruminal and arterial concentrations and net hepatic flux of butyrate increased with increasing butyrate infusion. Concentrations of glucose and a-amino-N in arterial blood decreased as butyrate infusion increased. Of the ruminal butyrate infused, 24.5% appeared in portal blood as butyrate. Acetoacetate, D-β-hydroxybutyrate, and a-amino-N were the nutrients most altered by increasing ruminal butyrate.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Butyrate; Volatile fatty acids; Bloodflow; Nutrients; Rumen